Locating climate adaptation in urban and regional studies. Issue 4 (2nd April 2020) - Kythreotis, Andrew P.; Jonas, Andrew E. G.; Howarth, Candice
ABSTRACT: This paper adds new insights to the relationship between city-regionalism, the territorial logics of the competition state and how climate adaptation is located in state spaces. Whilst climate adaptation governance is positioned within national economic sectors, it highlights an emerging city-regional policy dimension to such governance. The spatial reconfiguration of climate change adaptation governance reflects a tension between three quite distinct processes: (1) the sector-driven territorial logic of the national competition state; (2) the emergence of city-regionalism as an adaptation governance response to increased competition; and (3) the assertion of 'national' political priorities in the implementation of climate adaptation across subnational territories. Future climate adaptation governance research needs to address the uneasy relationship between the rise of city-regionalism and the sector-led priorities of the competition state.